EFECTIVIDAD DE LA APLICACIÓN DE LOS PRINCIPIOS CONSTITUCIONALES DE LA ADMINISTRACIÓN PÚBLICA EN LA CONTRATACIÓN PÚBLICA¨ - Aguinsaca Satama, Cinthia Fernanda (2019)
This research constitutes a final report of the research process carried out and motivated in Ecuadorian legislation, the same one that is entitled: ¨ effectiveness of the application of the constitutional principles of the public administration in the ¨ public procurement, its importance lies in the knowledge of a legal problem in the organic Law of the National Service of public procurement, regulation of the Organic Law of the National Service of public procurement since there are not established public policies that regulate certain procedures of the public procurement, of common system and special regime. Public procurement constitutes an important sector of the economic and social activity of a country, because it covers all the management of public resources, which represent significant amounts within the General State budget, whose impact reaches Direct results in the living conditions of the society, reason why it deserves to have more attention on the effectiveness of its application and even more if there is a real applicability of the constitutional principles governing public administration in public procurement processes. It is more convenient that, in some cases, the state acquires goods abroad, so the lack of regulation in international contracting matters is a constraint for the fulfillment of the activities of the public entities. The loss of public sector credibility as a citizen welfare manager is accompanied by demonstrations that demand and force public institutions to act by applying principles of economy, efficiency and effectiveness. These new demands, increasingly important as a result of the magnitude of the public deficit in virtually all countries, had at first a significant impact on public policy-building processes, but at the present time They are Contratación Pública Universidad Nacional de Loja 5 not confined solely to the political or ministerial sphere, but have been extended to all the actions of the administration in its different territorial orders. Thus, state, regional, provincial and local administrations are involved in processes of regeneration, change. New patterns of action and behavior, common internationally, are those that have led to design a new public operating system, a new philosophy of action: the new public management. Within the public procurement procedures, it is evident that there is no complete effectiveness of the applicable principles of public procurement, since in its different processes it is necessary to develop a criterion of uniformity in the acquisitions of goods and services carried out by the different public entities in the country.